The correct answer is option D.
F(G(x)) denotes the composition of the two functions F(x) and G(x). The composition of two functions result in x, if the two functions are inverses of each other. So in this case F(x) and G(x) will be the inverse of each other. So option D is the correct answer.
Answer: (X) = y => b^y = x
use that equation to get the exponential form
Step-by-step explanation:
Answer:Marquis Lafayette
Step-by-step explanation:
This shouldn't be in mathematics?
Answer:
![6\frac{14}{100}](https://tex.z-dn.net/?f=6%5Cfrac%7B14%7D%7B100%7D)
Step-by-step explanation:
First, you make fourteen a fraction.
![\frac{14}{100}](https://tex.z-dn.net/?f=%5Cfrac%7B14%7D%7B100%7D)
Then, make it a mixed fraction by adding a six.
![6\frac{14}{100}](https://tex.z-dn.net/?f=6%5Cfrac%7B14%7D%7B100%7D)
Lastly, have a great day! :)